If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6m + -6) = -108 Reorder the terms: 6(-6 + 6m) = -108 (-6 * 6 + 6m * 6) = -108 (-36 + 36m) = -108 Solving -36 + 36m = -108 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 36m = -108 + 36 Combine like terms: -36 + 36 = 0 0 + 36m = -108 + 36 36m = -108 + 36 Combine like terms: -108 + 36 = -72 36m = -72 Divide each side by '36'. m = -2 Simplifying m = -2
| 4x^2-25=-4x+10 | | x-31+x+43+x=180 | | -8+9a+-16a-17a+-3a=20 | | 11/6=x/11 | | 4x^3-25=-4x+10 | | 4[e+4]=-12 | | 29.96+x=26.95 | | 7a^2+28a-35=0 | | -8a+9a+(-16a)-17a+(-3a)=20 | | 4x-25=-4x+10 | | 6(j-7)-13=43 | | 2x+2(-1)=12 | | 4/7u=28 | | 2(-2)+2y=12 | | 200n=70 | | 204=-x+276 | | 3e^2x+1=9 | | 1.042=x(1-x) | | 9(2p+3)=81 | | 37=5m-63 | | 10c^2-33ct+20t^21= | | -7b-12=-4 | | 116=5v+16 | | (4x+5y)+(2x-11y)= | | 6a^2-15a-1=0 | | (5x-3)(x-2)(x+1)X=0 | | 6x+32=122 | | -11(26x-52)=44(-9x+3) | | 6p*3= | | 48/3=x/4 | | 5+3(-2)=-1 | | 30+0.35c=72 |